The Effect of Health Education using Leaflet Media on Adolescent Girls Knowledge about the Benefits of Abdominal Stretching Exercises during Menstruation at MTS Hasyim Asy'ari Kembangbahu Districts, Lamongan - Asyaul - wasiah; Maulidya Izzatus Shodiq (STRADA : Jurnal Ilmiah Kesehatan, 2022)
Abdominal stretching exercise is one of the relaxation techniques that can be used to reduce pain. The purpose of this study was to determine the effect of health education through leaflet media on the knowledge of Young Women about the benefits of Abdominal Stretching Exercises During Menstruation at Mts Hasyim Asy'ari Kec. Kembangbahu, Kab. Lamongan. This study uses a quasi-experimental method with a one group pretest-post test design, the population is all young women in Mts Hasyim Asy'ari Kec. Kembangbahu, Kab. Lamongan. And the number of samples is 31 people. In this study, researchers used a questionnaire sheet. Data analysis technique with Wilcoxon test. Based on the results of statistical tests obtained positive rank with Asymp Sign 2 tailed of 0.000. So it can be concluded that there are differences in the knowledge of young women before and after the intervention.